2020
DOI: 10.3390/ma13245590
|View full text |Cite
|
Sign up to set email alerts
|

Review on Adhesives and Surface Treatments for Structural Applications: Recent Developments on Sustainability and Implementation for Metal and Composite Substrates

Abstract: Using adhesives for connection technology has many benefits. It is cost-efficient, fast, and allows homogeneous stress distribution between the bonded surfaces. This paper gives an overview on the current state of knowledge regarding the technologically important area of adhesive materials, as well as on emergent related technologies. It is expected to fill some of the technological gaps between the existing literature and industrial reality, by focusing at opportunities and challenges in the adhesives sector,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 177 publications
0
42
0
Order By: Relevance
“…The CLT study highlights the importance of the adhesive. Marques et al (2020) state that this component is the most important part of a glued joint and emphasize that it depends on the formulation, preparation and application. Among the most requested, phenol-formaldehyde stands out, which is one of the main types of synthetic thermoset adhesive used by the wood panel industries.…”
Section: Introductionmentioning
confidence: 99%
“…The CLT study highlights the importance of the adhesive. Marques et al (2020) state that this component is the most important part of a glued joint and emphasize that it depends on the formulation, preparation and application. Among the most requested, phenol-formaldehyde stands out, which is one of the main types of synthetic thermoset adhesive used by the wood panel industries.…”
Section: Introductionmentioning
confidence: 99%
“…Acid etching, corona discharge treatment, plasma treatment, flame treatment and laser treatment are examples of surface treatments that aim to decrease the water contact angle and increase the surface tension. [258,259] In terms of aluminium alloys, Critchlow and Brewis [260] presented a review of surface treatments, which involved mechanical, chemical or electrochemical treatments. These authors concluded that, regardless of its effectiveness, the surface treatment must be selected according to the type of aluminium and adhesive to obtain the highest strength and durability.…”
Section: Potential and Challengesmentioning
confidence: 99%
“…For example: slow cure times; limited shelf life; and low humidity‐, solvent‐, and temperature‐resistance can be detrimental in many contexts. [ 4 ] Furthermore, there are increasing concerns for the sustainability and life‐cycle management of polymer‐based adhesives. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Furthermore, there are increasing concerns for the sustainability and life‐cycle management of polymer‐based adhesives. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation